Feasibility of intravitreal erythropoietin injections in humans. Issue 12 (18th August 2009) - Lagrèze, W A; Feltgen, N; Bach, M; Jehle, T
Abstract : Background/aims: Preclinical data suggest that intravitreally administered erythropoietin (EPO) is both neuroprotective and safe. In a small pilot series, we intended to assess the feasibility of intravitreal EPO injections in humans. Methods: Three patients with acute vascular occlusion of the posterior pole received a single intravitreal EPO injection of 2000 U. Immediately before the injection and over the ensuing 3 months, these patients were closely monitored by measuring visual acuity, visual fields, intraocular pressure, the electroretinogram, the haematocrit and serum EPO levels. Results: Over the observational period, most parameters remained unchanged except for a short-term rise of serum EPO levels, which, however, did not exceeded normal serum levels. No injection-related toxicity was observed. Conclusion: Based on this limited set of data, a single EPO injection of 2000 U, a dose adapted from previous in vivo studies, is feasible and seems to induce no obvious damage. Hence, further investigations of this therapeutic approach appear justified.